Accretion-induced merger leading to core-collapse supernovae in old stellar populations. Issue 3 (24th December 2021) - Braudo, Jessica; Bear, Ealeal; Soker, Noam
ABSTRACT: We examine a triple-star evolution that might lead to core-collapse supernovae (CCSNe) in stellar populations that are too old to allow for single or binary evolution to form CCSNe, i.e. where the most massive stars that evolve off the main sequence have masses of $\simeq 4\!-\!5\, {\rm M}_\odot$ . In the scenario we examine the most massive star in the triple system, of mass $\simeq 4\!-\!5\, {\rm M}_\odot$, transfers mass to an inner binary system at an orbital separation of $\simeq 100\!-\!1000\, {\rm R}_\odot$ . The initial orbital separation of the inner binary is $\simeq 10\!-\!50\, {\rm R}_\odot$ . The inner binary accretes most of the mass that the primary star loses and the two stars expand and their mutual orbit contracts until merger. The merger product is a main-sequence star of mass $\simeq 8\!-\!10\, {\rm M}_\odot$ that later experiences a CCSN explosion and leaves a neutron star (NS) remnant, bound or unbound to the white dwarf (WD) remnant of the primary star. We estimate the event rate of this WD–NS reverse evolution scenario to be a fraction of ≈5 × 10 −5 of all CCSNe. We expect that in the coming decade sky surveys will detect one to five such events.